Self-organized organic semiconductors : from materials to device applications - Li, Quan, 1965- (Hoboken, N.J. : John Wiley & Sons, 2011)
'This book focuses on the exciting topic on self-organized organic semiconductors - from materials to device applications. It offers up-to-date and accessible coverage of self-organized semiconductors for organic chemistry, polymer science, liquid crystals, materials science, material engineering, electrical engineering, chemical engineering, optics, optic-electronics, nanotechnology and semiconductors. Chapters cover chemistry, physics, processing, and characterization. The applications include photovoltaics, light-emitting diodes (LEDs), and transistors'--
Includes bibliograpical references and index.
Keywords: Organic semiconductors; Self-assembly (Chemistry); Self-organizing systems